Utilization of the Brazilian public health system by privately insured individuals: a literature review - Leonardo Ferreira Fontenelle; Thiago Dias Sarti; Maria Beatriz Junqueira de Camargo; Ethel Leonor Noia Maciel; Aluísio J. D. Barros (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
Abstract: More than one in four Brazilians have private health insurance (PHI), even thought it covers mostly the same procedures as the Brazilian Unified National Health System (SUS). This literature review included articles and monographs published since 1990 about the utilization of SUS by privately insured individuals. Considering outpatient care and hospitalization, privately insured people in Brazil use SUS in approximately 13% of the times they receive health care, and approximately 7% of people receiving care paid by SUS are privately insured; these findings vary depending on the type of service studied and on study methods. Utilization of SUS is more frequent in less developed regions, by people with more restricted PHI plans and by people with worse health status. Privately insured people report the limitations of PHI plans as their reasons for resorting to SUS. Sometimes, beneficiaries of PHI plans owned by nonprofit hospitals (which also provide health care financed by SUS) have easier access to care than uninsured people financed by SUS. Anecdotally, privately insured people are satisfied with SUS, but not to the point of adopting SUS as their preferred source of care. In short, for privately insured people, SUS only plays a secondary role in their health care. Despite PHI taking over part of the SUS's health care demand, PHI represents a restriction of the universal, equitable character of the SUS.